If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -1x = 5x + 1 Reorder the terms: 1 + -1x = 1 + 5x Add '-1' to each side of the equation. 1 + -1 + -1x = 1 + -1 + 5x Combine like terms: 1 + -1 = 0 0 + -1x = 1 + -1 + 5x -1x = 1 + -1 + 5x Combine like terms: 1 + -1 = 0 -1x = 0 + 5x -1x = 5x Solving -1x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -1x + -5x = 5x + -5x Combine like terms: -1x + -5x = -6x -6x = 5x + -5x Combine like terms: 5x + -5x = 0 -6x = 0 Divide each side by '-6'. x = 0 Simplifying x = 0
| 6x-89=3x-8 | | -18-10x=73-31x | | 113-5x=4x+5 | | 1-x=5x-1 | | X^2+6x+4=5 | | sin(a)+sin(b)=1 | | (x-8)(x-1)=0 | | 71-4x=14x+21 | | 2x+12=-15x-7 | | =16x^3-20x^2-4x+15 | | 2(p+1)=16 | | 2x+-9=33 | | 2x*2x-6x+8=0 | | 5x-3=3+10 | | 12a*(-6bc)-4a= | | 1x-70=6 | | 1x-70=2 | | 20(x-6)=15x | | -3x-2(-x-5)+10= | | (x^2)-6x=7 | | 14-4(2x+3y)= | | 2x+10=68 | | 2x+15=117 | | 2x+15=67 | | 2x+15=50 | | m-4m-2m-9= | | 3+6(5a+4an)+9na= | | 12x+16=4x-16 | | 798=-3x-84y | | w(w+4)=96 | | 2x+26=6x+42 | | x^3-3x^2-50=0 |